2021
DOI: 10.1016/j.cmi.2021.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Cross-resistance to cefiderocol and ceftazidime–avibactam in KPC β-lactamase mutants and the inoculum effect

Abstract: Objectives: Ceftazidimeeavibactam (CZA) and cefiderocol are recently commercialized molecules active against highly drug-resistant bacteria, including carbapenem-resistant members of the Enterobacteriaceae. Mutants resistant to CZA have been described, notably in Klebsiella pneumoniae carbapenemase (KPC) producers. Considering the structural similarities between ceftazidime and cefiderocol, we hypothesized that resistance to CZA in KPC-producing members of the Enterobacterales may lead to crossresistance to ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 13 publications
4
48
0
Order By: Relevance
“…The inoculum effect is defined as attenuation of antibacterial activity at higher bacterial densities above those used for susceptibility testing (>5 × 10 5 colony-forming unit [CFU]/mL) ( 19 ). This phenomenon is generally attributed to β-lactam antibiotics, especially cephalosporins, and has been recently described for cefiderocol ( 20 ). Higher bacterial density may increase the tolerant subpopulations and, thus, increase the chances of spontaneous mutations conferring resistance or leading to a more efficient enzymatic degradation of the antibiotic substance.…”
Section: Resultsmentioning
confidence: 82%
“…The inoculum effect is defined as attenuation of antibacterial activity at higher bacterial densities above those used for susceptibility testing (>5 × 10 5 colony-forming unit [CFU]/mL) ( 19 ). This phenomenon is generally attributed to β-lactam antibiotics, especially cephalosporins, and has been recently described for cefiderocol ( 20 ). Higher bacterial density may increase the tolerant subpopulations and, thus, increase the chances of spontaneous mutations conferring resistance or leading to a more efficient enzymatic degradation of the antibiotic substance.…”
Section: Resultsmentioning
confidence: 82%
“…Mutations in β-lactamases may also lead to CFDC resistance ( Figure 1 ). A 4- to 32-fold increase of an MIC90 was observed in D179Y-H274Y mutations of KPC-31 compared to the wild-type alleles reported by Hobson et al in 2021 ( 35 ). Shields et al have reported that the deletion of positions 292 and 293, which are located in the R2 loop of AmpC, causes the decreased susceptibility of Enterobacterales ( 38 ).…”
Section: Resistance Mechanismsmentioning
confidence: 68%
“…An MIC90 value at 16–64 mg/l was observed in a K. pneumoniae infected neutropenic murine thigh model, which was infected with 10 7 CFU/ml bacterial suspension ( 34 ). According to the EUCAST breakpoints, Hobson et al have also reported that high inocula (10 7 CFU/ml) with KPC-producing Enterobacteriaceae will lead the resistance to CFDC compared to usual inocula (10 5 CFU/ml) in 2021 ( 35 ).…”
Section: Reports Of In-vivo Resistance To Cfdcmentioning
confidence: 99%
“…In addition, Hobson et al pointed out the risk of cross-resistance with ceftazidime is caused by extension of KPC spectrum through specific mutations (namely KPC-31). Furthermore, they revealed a strong impact of a high-inoculum effect on CFDC MICs, which is even more worrisome [ 65 ]. Tiseo et al described a case of recurrent KPC- Kp bacteremia successfully treated with MVB after in vivo, CZA-induced resistance development to CZA and CFDC [ 44 ].…”
Section: Resultsmentioning
confidence: 99%